Supplemental Instruction Volume 1: Digital Technologies - Strømmen-Bakhtiar, Abbas; Helde, Roger; Suzen, Elisabeth (Waxmann Verlag, 2021)
Supplemental Instruction is a program designed to support students in their learning process. The program consists of advanced students supervising new students, where the purpose is to improve students' performance and reduce the risk of interruption of studies. Supplemental Instruction was established almost 50 years ago and is used today in universities around the world. This book is about the role, use and place of digital technologies in supplemental Instruction, which includes why we need Supplemental Instruction, teacher's integration of technology experience with lecture capture and more. The book is aimed at anyone who is concerned about study quality in higher education. The contributors are researchers and lecturers at various universities from several countries. This book is the first of a trilogy on Supplemental Instruction, where the themes for the other books are " Student Learning Processes" and "Organization and Leadership". The editors of the trilogy are Abbas Strømmen-Bakhtiar (Professor), Roger Helde (Associate Professor) and Elisabeth Suzen (Associate Professor), all three at Nord University, Norway.